Histomorphometric Assessment of the Impact of Bovine Demineralized Bone Graft on Bone Healing Versus Autogenous, Allogeneic and Synthetic Grafts in Experimentally- Induced Critical Size Bone Defects in Rats - M. Emre Benlidayı; Mehmet Kürkçü; Turgay Peyami Hocaoğlu; Sadık Gençoğlan; Murat Arslan (Cumhuriyet University, 2018)
Aim: Bone tissue has the ability to heal itself (regeneration) and may restore its morphology and function when injured. However, healing may be limited in the case of large wounds. A "critical-size defect" is an intraosseous wound in a particular bone and species of animal that will not heal spontaneously morphologically and functionally during the lifetime of the animal. Autogenous bone grafts have been regarded as "gold standard" for treatment of critical-size bone defects. Known drawbacks of autogenous bone graft have led to research efforts focusing on different graft materials and resulted in several alternative substitutes including xenografts, allografts and synthetic graft materials. The aim of the present study was to perform a histomorphometric study to investigate the effect of bovine demineralized bone graft on bone healing in comparison to autogenous, allogeneic and synthetic graft materials when applied into critical size bone defects with a diameter of 5 mm. Materials and methods: Experimental animals were divided into 4 groups, each having 8 rats. In the control group, a mandibular defect was created and then filled with a bovine graft (Integros Bone Plus XS Adana/Turkey). In the experimental groups, autogenous bone was reinserted into the critical-size defect which was created using a trephine bur in Group I (autogenous group) and Group II received a human graft (Korea Bone Bank (KBB) Gasandong Keumcheongu Seoul/South Korea) to fill the critical-size defect. For Group III, a synthetic bone graft β-tricalcium phosphate (Cerasorb North Carolina/USA) was applied on the critical-size bone defect. Specimens were obtained for histomorphometric examination and rats were sacrificed on day 28. Results: Histomorphometric examination performed on day 28 to evaluate the relative effects of different graft materials on new bone formation showed no significant difference in the volume of newly formed bone between groups receiving autogenous bone graft, allograft and bovine xenograft but a significant difference was observed versus synthetic bone graft group. Conclusion: While autogenous bone graft is currently regarded as the gold standard for bone regeneration, the difficulties in harvesting and application of autografts limit their use. Our results demonstrate that bovine bone graft may be used as a safe and effective alternative to autogenous bone graft.